GAMBARAN PELAKSANAAN GERAKAN MASYARAKAT HIDUP SEHAT DI DESA TLOGOREJO KECAMATAN BUTUH KABUPATEN PURWOREJO: GAMBARAN PELAKSANAAN GERAKAN MASYARAKAT HIDUP SEHAT DI DESA TLOGOREJO KECAMATAN BUTUH KABUPATEN PURWOREJO - Kurniawati, Nindi; Amanah, Siti (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
ESSENCE Research Background: The Healthy Living Community Movement (GERMAS) is an option in realizing a better level of public health. From the results of a preliminary study of 10 heads of families, it was found that 7 of them had not implemented the healthy living community movement well. Research Objective: To understand the description of the implementation of the Healthy Living Community Movement in Tlogorejo Village, Need District, Purworejo Regency based on the characteristics of the respondents. Research Method: This type of research uses a descriptive method. The total population is 133 heads of families and the sample is 100 heads of families, sampling using Simple Random Sampling Technique. Data was collected through checklist observations. The data analysis technique uses univariate analysis techniques with percentage formulas. Research Results: The implementation of the healthy living community movement in Tlogorejo Village, Need District, Purworejo Regency, was carried out by people who were in accordance with the theory, namely 27 heads of families (27.0%) and those who had not implemented the whole thing were 73 heads of families (73.0%). Conclusion: There is suitability to the theory of implementing the healthy living community movement, namely that 27 heads of families (27.0%) have carried out the healthy living community movement well and as a whole. Suggestion: For the public to be able to understand and improve the behavior of the healthy living community movement and be able to apply it in everyday life. Keywords: implementation, healthy living community movement